2021
DOI: 10.1016/j.rmed.2021.106638
|View full text |Cite
|
Sign up to set email alerts
|

ROX index as predictor of high flow nasal cannula therapy success in acute respiratory failure due to SARS-CoV-2

Abstract: Background : High-Flow Nasal Cannula (HFNC) therapy is useful treatment in patients with acute respiratory failure (ARF). The ROX index (ratio of pulse oximetry/fraction of inspired oxygen to respiratory rate) has been evaluated to predict success of HFNC in patients with pneumonia. Objective : The aim of this study was to determine whether the ROX Index could predict HFNC therapy success in patients with ARF due to SARS-CoV-2 pneumonia. Methods : An o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
3
31
1
1
Order By: Relevance
“…Ferrer et al 26 evaluated the usefulness of the ROX index in patients with a diagnosis of bilateral pneumonia with ARF due to SARS-CoV-2. The findings of the study showed that the ROX index is useful in assessing HFNC use in SARS-CoV-2 pneumonia, with a cut-off point of 5.35, after 24 hours with ventilatory support.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrer et al 26 evaluated the usefulness of the ROX index in patients with a diagnosis of bilateral pneumonia with ARF due to SARS-CoV-2. The findings of the study showed that the ROX index is useful in assessing HFNC use in SARS-CoV-2 pneumonia, with a cut-off point of 5.35, after 24 hours with ventilatory support.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, different parameters can be used for an accurate evaluation of the levels of severity, such as gas exchange values (PaO2/FiO2) or the ROX index (SO2/FiO2: respiratory rate). A higher ROX index (cut-off point of 5.35) on serial measurement within the first 24 hours of HFNO initiation, predicts the success of therapy in patients suffering from SARS-CoV-2-based pneumonia [ 2 ] while patients with low ROX index are more likely to experience HFNO failure in COVID-19-related respiratory failure [ 3 ].…”
mentioning
confidence: 99%
“…In an observational study by Ferrer et al .,[ 4 ] the authors included 85 patients having AHRF due to COVID19 and were initiated on HFNC. The authors observed that HFNC failed in 47 (55.3%) patients.…”
mentioning
confidence: 99%